1999
DOI: 10.1111/j.1460-2466.1999.tb02819.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Pretrial Publicity and Trial Outcomes

Abstract: Research suggests that pretrial publicity influences trials. Past research has relied heavily on experimental methods. Several commentators have questioned the ecological validity of the studies, and hence the value of the findings. The present study, one of the first to examine actual trials, focused on all federal murder trials over a 3-year period. The results suggested that (a) greater probability of conviction was associated with low rather than high levels of publicity; (b) defendants fared better under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
0
6
0
3
Order By: Relevance
“…Bruschke and Loges (2004) produced a book rejecting research claiming that pretrial publicity damages trial participants. In field surveys of their own, they found that when prejudicial pretrial publicity was rife in 134 federal murder trials (Bruschke & Loges, 1999) and in federal murder and robbery trials in three cities (Bruschke & Loges, 2001), verdicts showed no increased tendencies in the direction of the prejudicial publicity. In their studies, however, it was not possible for the researchers to document that the individuals who were exposed to the pretrial publicity also were the same people who were selected as jurors (although the researchers made efforts to show that the pools of subjects in each domain were comparable in many ways).…”
Section: Communication and The Lawmentioning
confidence: 95%
See 1 more Smart Citation
“…Bruschke and Loges (2004) produced a book rejecting research claiming that pretrial publicity damages trial participants. In field surveys of their own, they found that when prejudicial pretrial publicity was rife in 134 federal murder trials (Bruschke & Loges, 1999) and in federal murder and robbery trials in three cities (Bruschke & Loges, 2001), verdicts showed no increased tendencies in the direction of the prejudicial publicity. In their studies, however, it was not possible for the researchers to document that the individuals who were exposed to the pretrial publicity also were the same people who were selected as jurors (although the researchers made efforts to show that the pools of subjects in each domain were comparable in many ways).…”
Section: Communication and The Lawmentioning
confidence: 95%
“…Nevertheless, not all studies have consistently found significant effects for pretrial publicity (Bruschke & Loges, 1999Riedel, 1993;Shaffer, 1986), though occasionally the failure to find effects was simply the result of ceiling effects (Finkelstein, 1995). That is, in some studies, individual jurors were already so negatively disposed toward the defendant that additional shifts of sentiment against the defendant could not be registered.…”
Section: Communication and The Lawmentioning
confidence: 95%
“…Nevertheless, not all studies have consistently found significant effects for pretrial publicity (Bruschke & Loges, 1999Riedel, 1993;Shaffer, 1986), though occasionally the failure to find effects was simply the result of ceiling effects (Finkelstein, 1995). That is, in some studies, individual jurors were already so negatively disposed toward the defendant that additional shifts of sentiment against the defendant could not be registered.…”
Section: Communication and The Lawmentioning
confidence: 99%
“…Todavia, os trabalhos que tratam da questão apresentam perspectivas muito diferentes entre si. Podemos observar a tensão entre o direito e a mídia como uma crise da democracia contemporânea (Garapon, 1996a;1996b;1996c;Garapon e Salas, 1997;Salas, 1998); uma invasão do espaço judicial pelas câmeras de TV (Lassiter, 1996); uma cobertura de notícias sobre crimes cujo impacto ambiental é grande, mas não gera apelo mediático (Lynch et alii, 2000); uma relação entre o direito e a literatura (Aristodemu, 1993); pela ótica do sistema de justiça criminal como um objeto da cultura popular (Newman, 1990); da justificativa do veredicto de jurados na mídia (Marder, 1997); dos efeitos da publicidade anterior a julgamentos e seus veredictos (Bruschke e Loges, 1999); do tratamento legal de publicidade anterior a julgamentos (Chesterman, 1997); da distorção da verdade e da confusão entre fato e ficção em produtos culturais, e de suas implicações éticas (Cowan, 1998); das conexões entre a compreensão cotidiana do jurídico através da mídia e da sua relação com a ação legal (Steiner et alii, 1999).…”
Section: O Direito E a Mídiaunclassified